Management of Change Implemented in An Airline Company - Petruţa MIHAI; Oana VLĂDUŢ; Ana-Magdalena ANGHEL; Mihaela-Florentina DUŢU; Iulian-Claudiu DUŢU; Paula TUDOR (Communications of International Proceedings, 2022)
The process of change is vital within organizations, thus enabling them to satisfy the market requirements, to increase the shareholders’ worth, to fulfill their strategies and maintain stability, all for an efficient and durable development. Organizations need to initiate change processes to meet market demands, increase shareholder values, or pursue government strategies. They often need to initiate and implement change processes to maintain organizational stability and to support balanced economic growth and sustainable development. Change management is a process that allows an organization to change any part of its structure so that it can cope effectively in a constantly changing environment.
Keywords: change management; organization; forces of change.